A novel 3D-printed laryngoscope with integrated working channels for laryngeal surgery - Kienle, Linus L.; Schild, Leon R.; Böhm, Felix; Grässlin, Rene; Greve, Jens; Hoffmann, Thomas K.; Schuler, Patrick J. (Frontiers in Surgery, 2023)
Background: For the surgical treatment of early-stage laryngeal cancer, the use of transoral laser microsurgery (TLM) has emerged as the gold standard. However, this procedure requires a straight line of sight to the operating field and therefore a hyperextension of the patient’s neck. In a considerable number of patients, this is not possible due to anomalies in the cervical spine anatomy or soft tissue scarring e.g., after radiation. In these cases, adequate visualization of relevant laryngeal structures cannot be ensured using a conventional rigid operating laryngoscope, which may negatively affect the outcome of these patients. Methods: We present a system based on a 3D-printed prototype of a curved laryngoscope with three integrated working channels (sMAC). The curved profile of the sMAC-laryngoscope is specifically adapted to the nonlinear anatomy of the upper airway structures. The central working channel provides access for flexible video endoscope imaging of the operating field while the two remaining channels provide access for flexible instrumentation. In a user study (n = 11), visualization and reachability of relevant laryngeal landmarks as well as the feasibility of basic surgical procedures with the proposed system were examined in a patient simulator. In a second setup, the system was evaluated for its applicability in a human body donor. Results: All participants of the user study were able to visualize, reach and manipulate the relevant laryngeal landmarks. Reaching those took significantly less time in the second attempt compared to the first one (27.5s ± 5.2s vs. 39.7s ± 16.5s, p = 0.008) indicating a significant learning curve for handling the system. Instrument changes were performed quickly and reliably by all participants (10.9s ± 1.7s). All participants were able to bring the bimanual instruments into position for a vocal fold incision. Relevant laryngeal landmarks could be visualized and reached in the human body donor setup. Conclusion: Possibly, the proposed system may develop into an alternative treatment option for patients with early-stage laryngeal cancer and restricted mobility of the cervical spine in the future. Further improvements of the system could include finer end effectors and a flexible instrument with a laser cutting tool.